(untitled) (Research, Society and Development, 2020)
Objectives: to report a case of right colon cancer in a patient undergoing laparoscopic hemicolectomy at Hospital and Maternidade Dom Orione (HMDO), in the state of Tocantins and to discuss its clinical, evolutionary, diagnostic and therapeutic aspects, emphasizing the importance of early diagnosis to avoid disease progression. Methods: A case of right-side paraoscopic hemicolectomy is presented in a patient with ascending colon neoplasia, characterizing a retrospective study. For this purpose, the medical records located at Dom Orione Hospital and Maternity Hospital and Clínica Gastromed were used. Results: Male patient, 54 years old, went to the health team, reporting abdominal pain, moderate in the right hypochondrium, colic, insidious, without irradiation, associated with changes in bowel habits and anemia. Background: arterial hypertension, diabetes mellitus and acute myocardial infarction. After the hypothesis of colon neoplasia, colonoscopy was requested, which corroborated the initial hypothesis. The biopsy identified a moderately differentiated tubular adenocarcinoma. Laboratory tests were normal, except for the presence of microcytic and hypochromic anemia. Patient undergoing staging: CT scan of the chest and total abdomen without evidence of metastasis. CEA: 48.1 (up to 3.8 ng / mL). After being evaluated by Oncological Surgery, laparoscopic right hemicolectomy with lymphadenectomy, ileotransversion-lateral-lateral anastomosis and drainage of the cavity was indicated. Conclusion: Under the conditions that were carried out in the present study, we can conclude that the lapaoscopic route proved to be an effective method for the treatment of this patient with ascending colon neoplasia.